Assessment of continuous positive airway pressure effect on the circadian clock signaling pathway in obstructive sleep apnea patients - Agata Gabryelska; Szymon Turkiewicz; Adrian Gajewski; Julia Jaromirska; Dominik Strzelecki; Piotr Białasiewicz; Maciej Chałubiński; Marcin Sochal (Scientific Reports)
Abstract Obstructive sleep apnea (OSA) is associated with circadian rhythm dysregulation plausibly through affecting clock genes. The study’s purpose was to investigate the effect of one-night continuous positive airway pressure treatment (CPAP treatment) on circadian clock genes: BMAL1, CLOCK, CRY1, and PER1 at mRNA and protein levels. The study included 30 OSA patients, who underwent diagnostic polysomnography (PSG) and next a one-night effective CPAP treatment with PSG monitoring (CPAP). The blood was collected in the evening before and the morning after PSG and CPAP. Protein levels and mRNA expression were measured using ELISA and qRT-PCR, respectively. The increase in PER1 expression was observed in the morning after compared to the evening before CPAP (p = 0.005); additionally, PER1 protein level decreased in the morning after CPAP compared to the morning after PSG (p = 0.035). In CLOCK protein levels significant changes were observed: an increase in the morning after CPAP compared to the morning after PSG (p = 0.049), an increase in the morning after CPAP compared to the evening before (p = 0.006), and an increase in difference between the morning after and evening before CPAP vs. difference between morning after and evening before PSG (p = 0.012). Obtained results suggest that even short-term effective CPAP treatment might reverse circadian clock signaling pathway disruption in OSA.